The Qur'an Code: Strategi Iḥyā’ Al-Qur'an untuk Dakwah yang Tak Lekang Zaman - Alfikriah, Nurul Fathanah; Ghany , Abdul; Rosmini (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The primary challenge of contemporary Islamic propagation (dakwah) is maintaining the relevance of the Qur'anic message amidst the changing times. This study aims to dissect a strategic formulation in the effort to revive the values of the Qur'an (Iḥyā’ Al-Qur’an) as an epistemological foundation for propagation that remains current. Through a qualitative research method with a library research approach, this study analyzes the Living Qur'an framework as a concrete manifestation of Iḥyā’ Al-Qur’an, which integrates the dimensions of text, interpretation, and the sociocultural reality of the Muslim community. The findings indicate that this approach serves as an operational